PENGARUH KEMASAN DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN KOPI PADA PUJA COFFEE & CO. DI KABUPATEN SERANG - Abdul Aziz; Apostel Paulus Pardomuan Nainggolan (Universitas Bina Bangsa, 2022)
The many of coffee shops in Serang District, makes the level of business competition increase. Likewise in Cikande District, one of the existing coffee shops is called Puja Coffee must be able to captivate the hearts of both old and potential customers so that Brand Awareness is embedded. One of them is by making attractive packaging and arranging effective promotions. This study aims to analyze the conditions of consumer opinion, the independent variables, namely packaging, and promotion which have a positive and significant influence on the purchasing decision of Puja Coffee. In this study, the researcher uses a survey method and uses a questionnaire as the main data collection tool. The researcher used a correlational quantitative approach. This study took a sample of 66 respondents. Based on the results of research that has been carried out using SPSS version 25, it can be concluded that Packaging (X1) and Promotion (X2) are able to contribute 30.5% to Purchase Decisions (Y), and the remaining 69.5% is explained by other variables not included in the model. Based on the results of the F test, it shows that the two independent variables, namely Packaging and Promotion, simultaneously have a positive and significant effect on purchasing decisions